PANTANG LARANG AND THE ENVIRONMENTAL WISDOM OF SAMBASNESS MALAY IN THE SEPINGGAN VILLAGE - Kurniawan, Syamsul (KALAM, 2018)
Based on the research, Sambasness Malay in Sepinggan Village recoqnize pantang larang (prohibition/taboo) as moral norms or unwritten rules dealing with their activities as Malay. it is called pantang larang  because it contains prohibition. If someone breaks the rules of pantang larang, he or she will get bad or scary thing. At sepinggan village,pantang larang developed as a strategy for malay in educating character building indeed since early childhood. The environmental wisdom is one of things which reflected in Sambasness Malay's pantang larang at Sepinggan Village. It has been known for a long time from desecent untill now and internalized assimilated in their activities as moeslims. it is descriptive research. it describes objective and contextual that information source gains from the field observation.